2022
DOI: 10.2340/jrm.v54.2040
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health Conditions in Persons with Spinal Cord Injury Across 21 Countries Worldwide

Abstract: Objectives: To describe the three-month prevalence and correlates of self-reported physical health conditions in persons with spinal cord injury (SCI) worldwide.  Study design: Multinational cross-sectional survey. Subjects: Community living persons with traumatic or non-traumatic SCI aged > 18 years from 21 countries representing all the six World Health Organization regions. Methods: We used data from 11 058 participants in the International SCI Community Survey (InSCI). The survey, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
22
0
2
Order By: Relevance
“…This can be attributed to hindered mobility, urinary and fecal incontinence, sensitivity, pain, embarrassment towards their own body, low self-esteem, difficulty reaching orgasm, and difficulty maintaining lubrification 27,28 . Furthermore, this result shows that interventions in sexual dysfunction after SCI should be developed, as international studies have found that sexual dysfunction exhibited the highest self-reported level of severity, but with the lowest treatment rate 29 .…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…This can be attributed to hindered mobility, urinary and fecal incontinence, sensitivity, pain, embarrassment towards their own body, low self-esteem, difficulty reaching orgasm, and difficulty maintaining lubrification 27,28 . Furthermore, this result shows that interventions in sexual dysfunction after SCI should be developed, as international studies have found that sexual dysfunction exhibited the highest self-reported level of severity, but with the lowest treatment rate 29 .…”
Section: Discussionmentioning
confidence: 73%
“…Recently, a multinational cross-sectional survey, described the prevalence and correlates of self-reported physical health conditions in persons with spinal cord injury (SCI) from 21 countries, representing all the 6 World Health Organization regions, with 11,058 participants in the International SCI Community Survey (InSCI) 29 . The survey, based on the International Classification of Functioning, Disability and Health (ICF) Core Sets for SCI identified that 95.8% of the participants reported having experienced 1 or more health problems secondary to SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spasticity is characterized by a velocity-dependent increase in tonic stretch reflexes (muscle tone) with exaggerated tendon jerk ( Feldman et al, 1980 ). Roughly, the prevalence of spasticity reaches to 42.6% ( Harb and Kishner, 2022 ) in stroke patients, and 73.5% of patients with SCI may accompany spasticity ( Strom et al, 2022 ). Moreover, approximately 80% of patients with MS ( Arroyo González, 2018 ) and 69.8% children with CP ( Pulgar et al, 2019 ) experience spasticity.…”
Section: Introductionmentioning
confidence: 99%